Influence of Pore Geometry on Sandstone Pore Analysis Based on a Digital Core - Liu, Xuechao; Ren, Dazhong (Frontiers in Physics, 2022)
Digital core obtained without damage and contact can provide intuitive and quantitative analysis data for sandstone pore structure analysis. However, pore analysis results based on digital cores are quite different from experimental results due to the limitations of scanning resolution, scanning quality, pore extraction method and experimental errors. In this paper, the influence of pore geometry on pore analysis is studied from pore angle, pore resolution. Firstly, the sharp angle is extracted by image processing method, and the influence of pore angle on pore radius distribution is analyzed. Then, by up-down sampling, high and low resolution digital cores are reconstructed and the effect of resolution on pore connectivity and throat structure is discussed. In this paper, the influence of pore morphology in digital core is analyzed by simulation.